PERLINDUNGAN HAK ANAK AKIBAT PSIKOTROPIKA - Lembong, Roy Ronny (LEX CRIMEN, 2012)
Protecting children today, means protecting society, country and nation in the future. In general, every children without any exception have an equal right to be protected by law, whether children as a victim, or children as an offender as well. Sometimes, Â people ignore protection need of children who is involved some cases in law, because they think children such as that category will bring some problems to their society, and has been labeled as a criminal. Absolutely, their opinion is wrong indeed. We do not generalize or juxtapose children such as that category as well as a criminal. According to Children Rights Convention (CRC), Children in a conflict with the law has set as one of Â category children who is in need a special protection. Children in a conflict with the law or in other words called by â€œJuvenille delinquencyâ€ need a prior protection more than any normal children. Protection ofÂ  normal children,Â  children as a victim, and children in conflict is regulated by and based on anyÂ  different regulations/instrument Internationally and nationally. One of International regulation/instrument is called by Beijing Rules, WhereasÂ  there are several regulation which is implemented to give some protectionÂ  to children In Indonesia, such as Undang-undang Nomor 5 Tahun 1997. Keywords: Children, victim, psychotropica